Loss of BOK Has a Minor Impact on Acetaminophen Overdose-Induced Liver Damage in Mice - Naim, Samara (Int J Mol Sci, 2021)
Acetaminophen (APAP) is one of the most commonly used analgesic and anti-pyretic drugs, and APAP intoxication is one of the main reasons for liver transplantation following liver failure in the Western world. While APAP poisoning ultimately leads to liver necrosis, various programmed cell death modalities have been implicated, including ER stress-triggered apoptosis. The BCL-2 family member BOK (BCL-2-related ovarian killer) has been described to modulate the unfolded protein response and to promote chemical-induced liver injury. We therefore investigated the impact of the loss of BOK following APAP overdosing in mice. Surprisingly, we observed sex-dependent differences in the activation of the unfolded protein response (UPR) in both wildtype (WT) and Bok(-/-) mice, with increased activation of JNK in females compared with males. Loss of BOK led to a decrease in JNK activation and a reduced percentage of centrilobular necrosis in both sexes after APAP treatment; however, this protection was more pronounced in Bok(-/-) females. Nevertheless, serum ALT and AST levels of Bok(-/-) and WT mice were comparable, indicating that there was no major difference in the overall outcome of liver injury. We conclude that after APAP overdosing, loss of BOK affects initiating signaling steps linked to ER stress, but has a more minor impact on the outcome of liver necrosis. Furthermore, we observed sex-dependent differences that might be worthwhile to investigate.